2000
DOI: 10.1128/jvi.74.23.11388-11393.2000
|View full text |Cite
|
Sign up to set email alerts
|

Role of Simian Virus 40 Vp1 Cysteines in Virion Infectivity

Abstract: We have developed a new nonoverlapping infectious viral genome (NO-SV40) in order to facilitate structurebased analysis of the simian virus 40 (SV40) life cycle. We first tested the role of cysteine residues in the formation of infectious virions by individually mutating the seven cysteines in the major capsid protein, Vp1. All seven cysteine mutants-C9A, C49A, C87A, C104A, C207S, C254A, and C267L-retained viability. In the crystal structure of SV40, disulfide bridges are formed between certain Cys104 residues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 21 publications
2
44
1
Order By: Relevance
“…We have previously shown that mutating Cys254, a residue located on a conserved loop near the calcium sites, can severely reduce the formation of infectious particles. That this defect is observed for substitution into certain side chains (leucine, glycine, serine, and arginine) but not into alanine is consistent with the local structure of Cys254, including the putative calcium-binding residues, being important for particle assembly and infectivity (17). Mutating certain acidic residues of the calcium-binding sites also affects the shape or stability of virus-like particles (VLPs) formed in Vp1-expressing insect cells (12).…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…We have previously shown that mutating Cys254, a residue located on a conserved loop near the calcium sites, can severely reduce the formation of infectious particles. That this defect is observed for substitution into certain side chains (leucine, glycine, serine, and arginine) but not into alanine is consistent with the local structure of Cys254, including the putative calcium-binding residues, being important for particle assembly and infectivity (17). Mutating certain acidic residues of the calcium-binding sites also affects the shape or stability of virus-like particles (VLPs) formed in Vp1-expressing insect cells (12).…”
mentioning
confidence: 79%
“…Viability was determined by plaque formation assays using serial dilutions of lysates prepared by freezethawing NO-SV40 DNA-transfected CV-1 monkey kidney cells at 72 h posttransfection, as described previously (17,18). For select NO-SV40 mutants, plaques were lifted from the culture dish, resuspended in 0.1 to 1.0 ml of TD buffer, and lysed by freeze-thawing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of mature viral particles was detected by sedimentation velocity ultracentrifugation as previously reported (Li et al, 2000). Briefly, nuclei were isolated from infected cells, sonicated and overlayed onto 5-32% sucrose gradients (50 mM N-[2-Hydroxyethyl]piperazine-N'-[2-ethanesulfonic acid] (HEPES) buffer, pH 7.5) in a SW41 tube.…”
Section: Sucrose Gradient Ultracentrifugationmentioning
confidence: 99%
“…The pentamers are linked to each other by the interchain disulfide bonds between the residues Cys104. Isomerization of the disulfide bonds in the ER is crucial for the viral uncoating process [136][137][138]. Recent data has shown that SV40 makes use of the protein folding and quality control machinery in the ER for initial uncoating and membrane translocation [46].…”
Section: Sv40mentioning
confidence: 99%